Omeprazole vs. Pantoprazole for stress ulcer prophylaxis in critically ill patients: a clinical and pharmacoeconomic analysis (Research, Society and Development, 2024)
Objective: To compare the use of Omeprazole and Pantoprazole in the context of prophylaxis of acute gastric mucosal injury from the perspective of clinical outcomes and pharmacoeconomics in the intensive care setting in Brazil. Method: A retrospective cohort and pharmacoeconomic study was conducted in the Intensive Care Units (ICU) of a high-complexity hospital in the Northeast region of Brazil, using the years 2021 and 2022 as the reference period. The primary outcome assessed was the incidence of upper gastrointestinal bleeding (UGIB). Secondary outcomes included ICU length of stay, 90-day mortality in the ICU, and incidence of adverse events related to acid suppression: ventilator-associated pneumonia (VAP) and Clostridium difficile infection (CDI). Additionally, a pharmacoeconomic study was performed using a cost-minimization analysis. Results: There were no significant differences in the incidence of UGIB between the groups (2.6% vs. 3.8%, p-value = 0.999), nor in the incidence of VAP (15.4% vs. 20.5%, p-value = 0.999), CDI (2.6% vs. 1.3%, p-value = 0.989), ICU length of stay (p-value = 0.519), and 90-day ICU mortality (30.8% vs. 24.4%, p-value = 0.370). However, Omeprazole was found to be less costly than Pantoprazole, both during the study period (Cost savings – min/max: $13,351.15/$16,398.45) and in current projections (Cost savings – min/max: $17,119.02/$21,257.68). Conclusion: Our study demonstrates that Omeprazole and Pantoprazole have similar safety and efficacy profiles for the prophylaxis of acute gastric mucosal injury. Considering the lower associated costs, we propose adopting Omeprazole as the preferred medication in this context.